1998
DOI: 10.1007/bf02281123
|View full text |Cite
|
Sign up to set email alerts
|

Short-term variability of blood pressure and heart rate in hyperthyroidism

Abstract: The effect of hyperthyroidism on the short-term memory variability of blood pressure and heart rate was evaluated in 12 untreated hyperthyroid patients during thyrotoxicosis and after a 6 1/2 month treatment designed to achieve a stable euthyroid state. Beat-by-beat finger blood pressure was measured with a Finapres device. The pulse interval, from which pulse rate was derived, was obtained from the blood pressure signal. Due to the significant change in heart rhythm associated with thyrotoxicosis, both pulse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
1
5
1
Order By: Relevance
“…Our data showed increased LF/HF and decreased HF component in the hyperthyroid patients compared with the controls, denoting a sympathovagal imbalanced state and depressed vagal modulation of the heart rate in hyperthyroidism. Our findings are consistent with prior studies performed by Cacciatori et al, 23 Inukai et al, 24 Girard et al 25 and Burggraaf et al 26 In addition, early studies on tachycardia of hyperthyroidism 12,13,[28][29][30] and results from the 24-h Holter monitoring studies by time-domain analysis of HRV 31,32 all reported a reduced vagal modulation of heart rate in hyperthyroidism. In comparison, Pitzalis et al showed no difference in HF% for hyperthyroid patients and concluded that hyperthyroid patients did not have impaired cardiac vagal activity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data showed increased LF/HF and decreased HF component in the hyperthyroid patients compared with the controls, denoting a sympathovagal imbalanced state and depressed vagal modulation of the heart rate in hyperthyroidism. Our findings are consistent with prior studies performed by Cacciatori et al, 23 Inukai et al, 24 Girard et al 25 and Burggraaf et al 26 In addition, early studies on tachycardia of hyperthyroidism 12,13,[28][29][30] and results from the 24-h Holter monitoring studies by time-domain analysis of HRV 31,32 all reported a reduced vagal modulation of heart rate in hyperthyroidism. In comparison, Pitzalis et al showed no difference in HF% for hyperthyroid patients and concluded that hyperthyroid patients did not have impaired cardiac vagal activity.…”
Section: Discussionsupporting
confidence: 93%
“…Accordingly, using spectral analysis of HRV, not only the vagal but also the sympathetic modulation of the heart rate can be observed. Among the few studies using spectral analysis of HRV to investigate the autonomic nervous system (ANS) functions in hyperthyroidism, some disclosed reduced vagal activity, 23–26 whereas others showed no vagal activity impairment 27 …”
Section: Introductionmentioning
confidence: 99%
“…Autonomic nervous system dysfunction has been described not only in cardiovascular disorders [1], but also in various endocrinologic [2,3] neurologic [4,5], and, recently, psychiatric disorders [6,8]. Several noninvasive tests of heart rate variability (HRV) are commonly used to evaluate cardiovascular autonomic nervous system (ANS) function, including well-established conventional tests (eg, maximum/minimum 30:15 ratio, deep breathing test, Valsalva maneuver) and standardized, computerized measurements of HRV involving spectral analysis.…”
Section: Received June 17 2000; Accepted As Revised March 22 2001mentioning
confidence: 99%
“…Production, release, degradation, and plasma concentrations of catecholamines were reported to be normal or even decreased in hyperthyroidism [2,3]. The well-known increase of heart rate in thyrotoxicosis may be caused not only by increase of intrinsic sinoatrial node activity but also by modulatory influences of the autonomic nervous system (ANS), among which decrease of physiological vagal inhibition of sinoatrial node seems to be essential [4][5][6]. This interpretation is supported by several findings: impaired central effect of low-dose atropine in subjects with hyperthyroidism [7], reduced capacity of vagal inhibition after selective pharmacologic blockade [8], and depression of the capacity for vagal withdrawal during exercise in the same subject group [9].…”
mentioning
confidence: 99%